2013
DOI: 10.3109/0142159x.2013.770130
|View full text |Cite
|
Sign up to set email alerts
|

The desirable qualities of future doctors – A study of medical student perceptions

Abstract: Background: There is a lack of consensus regarding the qualities possessed by the ideal doctor, and very limited research regarding the views of medical students on these qualities. Aims: To investigate the views of commencing medical students regarding the desirable qualities of doctors. Methods: A survey containing a set of proposed desirable qualities of doctors identified from the existing literature was completed by 158 first-year medical students. Results: The survey had a 75% response rate. Students rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 23 publications
3
25
0
2
Order By: Relevance
“…The results also showed that CBL improved the student's personal skills specially their communication skills which are known to be essential for medical as well as dental doctors [16].In line with our findings, it has been reported that student communication skills and ability to work within a team were significantly improved due to CBL implementation in a microbiology course [17][18] and pharmacology course [19].Our data indicated that this innovative pedagogical approach not only improved students' personal skills but also improved students' professionalism in the form of punctuality and respect of others opinions in the group.…”
Section: Results:-supporting
confidence: 80%
“…The results also showed that CBL improved the student's personal skills specially their communication skills which are known to be essential for medical as well as dental doctors [16].In line with our findings, it has been reported that student communication skills and ability to work within a team were significantly improved due to CBL implementation in a microbiology course [17][18] and pharmacology course [19].Our data indicated that this innovative pedagogical approach not only improved students' personal skills but also improved students' professionalism in the form of punctuality and respect of others opinions in the group.…”
Section: Results:-supporting
confidence: 80%
“…The range of desirable personal abilities of a doctor varied according to student characteristics including their prior educational experience. [6]…”
Section: Introductionmentioning
confidence: 99%
“…They are aware of this point. This is shown by Hurwitz et al, [2] who surveyed firstyear students regarding the desirable qualities of future doctors and reported that empathy received the second-highest score. Meanwhile, some previous studies have indicated a decline of students' empathy during undergraduate medical education [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 82%